PENGARUH TELEHEALTH TERHADAP PENGENDALIAN TEKANAN DARAH: The Effect of Telehealth on Blood Pressure Control - Dian Jayantari Putri K.Hedo; Rayi Apriananda; Rita Benya Adriani (Forind Press, 2024)
Hypertension is a chronic condition that attacks adults of all ages. Having an effective method or way to manage this condition is the key to successful treatment of hypertension. The design of this research is a cohort study that examines data on hypertensive patients obtained from health service databases. The research took place in October until December 2021. The inclusion criteria in this study were adults (≥45 years) with prehypertension and hypertension, residing in rural areas. An assessment was carried out on respondents who could access the telehealth application at home, and it was validated for monitoring blood pressure using mobile phone or other device with an internet connection that allows monitoring from the respondent's home and telehealth services. Respondents were asked to fill in the results of blood pressure measurements. Based on the results, 55 respondents (100%) carried out data collection. Linear regression analysis found an average reduction in systolic blood pressure of 19.2 mmHg. Respondents in the decreasing systolic blood pressure group had a higher frequency of self-measured blood pressure monitoring (OR = 0.85; 95% CI= 0.81 - 0.89; p = 0.002) than other patients. The use of telehealth at home combined with care management by health workers is considered effective in improving blood pressure control in hypertensive patients.